Urban Avant-Gardes : art, architecture and change - Miles, Malcolm (Routledge, 2004)
Can art or architecture change the world? Is it possible to think of a new cultural avant-garde today? This book contributes to the debate by looking back to past avant-gardes and by profiling contemporary cases of radical cultural practices.